Chemical abundances and radial velocities in the extremely metal-poor galaxy DDO 68. Issue 3 (30th October 2018) - Annibali, F; La Torre, V; Tosi, M; Nipoti, C; Cusano, F; Aloisi, A; Bellazzini, M; Ciotti, L; Marchetti, A; Mignoli, M; Romano, D; Sacchi, E
ABSTRACT: We present chemical abundances and radial velocities of six H ii regions in the extremely metal-poor star-forming dwarf galaxy DDO 68. They are derived from deep spectra in the wavelength range 3500–10 000 Å, acquired with the Multi-Object Double Spectrograph at the Large Binocular Telescope (LBT). In the three regions where the [O iii ] λ4363 Å line was detected, we inferred the abundance of He, N, O, Ne, Ar, and S through the 'direct' method. We also derived the oxygen abundances of all the six regions adopting indirect-method calibrations. We confirm that DDO 68 is an extremely metal-poor galaxy, and a strong outlier in the luminosity–metallicity relation defined by star-forming galaxies. With the direct method, we find indeed an oxygen abundance of 12+log(O/H) = 7.14 ± 0.07 in the northernmost region of the galaxy and, although with large uncertainties, an even lower 12 + log(O/H) = 6.96 ± 0.09 in the 'tail'. This is, at face value, the most metal-poor direct abundance detection of any galaxy known. We derive a radial oxygen gradient of −0.06 ± 0.03 dex kpc −1 (or −0.30 dex R_25^-1 ) with the direct method, and a steeper gradient of −0.12 ± 0.03 dex kpc −1 (or −0.59 dex R_25^-1 ) from the indirect method. For the α-element to oxygen ratios, we obtain values in agreement with those found in other metal-poor star-forming dwarfs. For nitrogen, instead, we infer much higher values, leading to log(N/O)∼− 1.4, at variance with the suggested existence of a tight plateau at −1.6 in extremely metal-poor dwarfs. The derived helium mass fraction ranges from Y = 0.240 ± 0.005 to Y = 0.25 ± 0.02, compatible with standard big bang nucleosynthesis. Finally, we measured H ii region radial velocities in the range 479−522 km s −1 from the tail to the head of the 'comet', consistent with the rotation derived in the H i .